2012
DOI: 10.1371/journal.pone.0030429
|View full text |Cite
|
Sign up to set email alerts
|

Krüppel-Like Factor 8 (KLF8) Is Expressed in Gliomas of Different WHO Grades and Is Essential for Tumor Cell Proliferation

Abstract: Krüppel-like factor 8 (KLF8) has only recently been identified to be involved in tumor cell proliferation and invasion of several different tumor entities like renal cell carcinoma, hepatocellular carcinoma and breast cancer. In the present study, we show for the first time the expression of KLF8 in gliomas of different WHO grades and its functional impact on glioma cell proliferation. In order to get information about KLF8-mRNA regulation qPCR was performed and did not reveal any significant difference in sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…Ki67 is a nuclear protein highly linked with cell proliferation and extensively used as a proliferation marker in human tumors (34,35). Following p75NTR knockdown by two p75NTR-siRNAs, there was a decrease in the proliferation rate of BTICs in vitro (Fig.…”
Section: Neurotrophin Receptors and Ligands Are Expressed In Brainmentioning
confidence: 99%
“…Ki67 is a nuclear protein highly linked with cell proliferation and extensively used as a proliferation marker in human tumors (34,35). Following p75NTR knockdown by two p75NTR-siRNAs, there was a decrease in the proliferation rate of BTICs in vitro (Fig.…”
Section: Neurotrophin Receptors and Ligands Are Expressed In Brainmentioning
confidence: 99%
“…As a GT-box (CACCC) binding dual-transcription factor, KLF8 regulates the transcription of numerous genes by recruiting the C-terminal binding protein (CtBP) corepressor (6-10) or p300 and P300/CtBP-associated factor histone acetyltransferase co-activators (8,(11)(12)(13)(14) in order to target gene promoters. It is aberrantly overexpressed in a number of cancer subtypes and has been implicated in the initiation, development and progression of these cancer subtypes, including hepatocellular carcinoma (15)(16)(17), gastric cancer (18)(19)(20)(21), breast cancer (22,23), ovarian cancer (14,24), renal cancer (22,25) and glioma (26). It is worth noting that KLF8 induced tumor cell epithelial-to-mesenchymal transition (EMT) and maintained the invasive potential of cancer, which appeared to serve a critical role in the metastatic progression of cancer cells (6,27).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, KLF8 has been shown to activate transcription from some gene promoters (21)(22)(23)(24). KLF8 is not expressed at readily detectable levels in most cell and tissue types studied to date (55), but numerous studies have reported its upregulation in various human cancers, including prostate (56), gastric (57,58), hepatocellular (59,60), glioma (61), breast (62,63), renal (64), and ovarian (65). KLF8 has been shown to regulate oncogenesis by promoting cellular proliferation and tumor invasion and by inhibiting apoptosis (21,(65)(66)(67)(68) Crossing these mice with Klf3 null mice results in embryonic lethality, indicative of a genetic interaction between these two factors.…”
mentioning
confidence: 99%